Pornography object detection using Viola-Jones algorithm and skin detection - Wiratama, Muhammad R.; Endah, Sukmawati N.; Kusumaningrum, Retno; Wibawa, Helmie A. (ICICoS : 2017 1st International Conference on Informatics and Computational Sciences : Santika Premiere Hotel, Semarang, Central Java, Indonesia, 15-16 November 2017, 2017)
Pornography can be an image that contains obscenity or sexual exploitation, so unwittingly can damage human morals, especially for children who are certainly not old enough. This is an important task for the community in dealing with, handling, or avoiding this negative character of pornography. One prevention in order to avoid pornography is to create application to detect pornography object. The method used in this application are Viola-Jones algorithm and skin detection. In the process, this application produced Region of Interest (ROI) from the process of detecting pornography object using the Viola-Jones pornography object detector, and the ROI is further processed into the skin detection stage. The test results show that this application has been able to detect pornography objects from an image with test accuracy value reaching 78.29% and the best parameters of pornography object detector training is False Alarm Rate parameter with value 0.05 and Number of Stages parameter with value 10.